Management of and indications for tracheostomy in care of the critically ill patient. Issue 4 (April 2018) - Timbrell, David; Jankowski, Stanislaw
Abstract: Tracheostomy is a procedure that has evolved over many hundreds of years. In the 21st century, the majority of tracheostomies are now inserted by intensivists in the intensive care unit (ICU). Commonly performed to assist in weaning patients from mechanical ventilation, the procedure is performed using a percutaneous dilatational technique. Percutaneous tracheostomy can generally be performed safely in the ICU, although a number of contra-indications and complications do exist. Recent publications have highlighted weaknesses in the quality of care both in the immediate and longer term. Consequently, a number of organizations, based in the UK and internationally, have turned the focus in recent years to improving the quality of care delivered to these patients. Clinicians caring for patients with tracheostomies should not only be familiar with the indications, anatomy and insertion techniques, but also current guidance on routine care and the emergency management of complications.